(untitled) (JOURNAL OF ADVANCES IN MATHEMATICS, 2015)
In this paper we establish a coupled coincidence point results for compatible mappings in a fuzzy metric spaces having a partial order relation defined on the space. The fuzzy metric space we use has a Hausdorff topology. The t-norm is used here is a Hadz̆i\’c type t-norm. Here we use \’Ciri\’c type inequality which has been considered in a good number of papers. Two control functions are also used. The main theorems have several corollaries. An illustrative example is given. The example establishes that the corollaries are actually contained the main theorem. We use a methodology which is a combination of order theoretic and analytic methods